Relación entre la evitación experiencial y el estrés académico en estudiantes de psicología clínica de la Universidad Nacional de Loja, periodo 2022-2023 - Silva Pauta, Romel Santiago (2023)
Experiential avoidance and academic stress are two phenomena that have generated interest in the scientific community due to their frequency among university students and their potential impact on health. In recent years, it has been shown that these two variables can play an important role in the development, maintenance, and aggravation of different psychological problems. In this context, the present research sought to determine the relationship between experiential avoidance and academic stress in undergraduate students of Clinical Psychology at the National University of Loja, during the period 2022 - 2023. A cross-sectional descriptive correlational design was employed, in which 174 students participated, they were selected by simple probability sampling. Two instruments were employed in the study: Acceptance and Action Questionnaire - II (AAQ-II) and the Systemic Cognitive Inventory for the study of academic stress. (SISCO SV-21). The results indicated a highly significant but low relationship, between experiential avoidance and academic stress. The most prevalent levels of experiential avoidance and academic stress were: mild experiential avoidance and moderate academic stress. Although the majority of students present mild experiential avoidance, there is a significant proportion of students who fall in the moderate to severe range, which should be considered a risk indicator due to the variety of psychopathologies that have been associated with this variable